Effects of Iron and Amloki (Emblica Officinalis) on Serum Zinc Level in Anaemia with Pregnancy (Medicine Today, 2021)
Introduction: Pregnancy is associated with several trace elements deficiency in developing countries. Supplementation of iron in iron deficiency anaemia (IDA) has several side effects including alterations of serum zinc level. Traditionally, amloki is used as a well known supplement in pregnancy, which is rich in trace elements. Aims were to determine the effects of iron and amloki on serum zinc level in IDA with pregnancy.Materials and Methods: This Prospective, longitudinal and interventional study was done by non blinded, non randomized sampling followed by inclusion and exclusion criteria. This study was performed in the Department of Physiology, Dhaka Medical College, Dhaka on 43 pregnant women between 13th to 20th weeks of gestation with IDA from July 2016 to June 2017. They were recruited from Outpatient Department of Obstetrics and Gynaecology of Dhaka Medical College Hospital. Anaemic pregnant women supplemented with oral iron and amloki were considered as study group (A) and control group (B) were with only iron supplementation for 45 days. Serum zinc level was estimated in the laboratory of the Department of Soil, Water and Environment, University of Dhaka, Dhaka. For statistical analysis, Paired Student’s ‘t’ test and Unpaired Student’s ‘t’ test were considered using SPSS 22.0 version.Results: Significant decrease (p